2021
DOI: 10.1007/s10668-021-01602-x
|View full text |Cite
|
Sign up to set email alerts
|

Green, blue or black, but washing–What company characteristics determine greenwashing?

Abstract: The purpose of this paper is to study what are the characteristics that make firms less or more prone to greenwashing. We collect data from sustainability disclosures of the S&P top 100 companies, to investigate the determinants of greenwashing. We use content analysis to measure the level of reporting of the companies. We define the “greenwashing” variable as the difference between what the company says it does in terms of commitment to sustainability, and what the company actually does as evaluated by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 80 publications
0
35
0
4
Order By: Relevance
“…CSR is a multi-level concept that can also be used interchangeably with sustainability (Strand et al, 2015). Research has shown that companies that operate in environmentally sensitive sectors participate in less greenwashing and that lower greenwashing is associated with higher-quality sustainability reporting (Ruiz-Blanco et al, 2022). Accordingly, there is an assumed link between sustainability reporting and CSR practices.…”
Section: Introductionmentioning
confidence: 99%
“…CSR is a multi-level concept that can also be used interchangeably with sustainability (Strand et al, 2015). Research has shown that companies that operate in environmentally sensitive sectors participate in less greenwashing and that lower greenwashing is associated with higher-quality sustainability reporting (Ruiz-Blanco et al, 2022). Accordingly, there is an assumed link between sustainability reporting and CSR practices.…”
Section: Introductionmentioning
confidence: 99%
“…Panel surveys can assess, over time, the marketing results of organizations that exhibit these CSR washing practices. Although it is not within the scope of bibliometric analysis, significant growth in the number of publications on this subject was noticed in the year 2021, indicating a real increase in interest in investigating this topic (e.g., [116][117][118][119][120]).…”
Section: Discussionmentioning
confidence: 99%
“…Second, to decrease those problems, other researchers recognized the difference between CSR reporting, based on manual content analyses, and CSR performance, based on external CSR databases ( Bloomberg , e.g., Ruiz‐Blanco et al, 2022; Morgan Stanley Capital International , Tashman et al, 2019), as CSR decoupling. Next to manual content analyses, automatized textual analyses to measure tone management in CSR reporting, for example, based on python and wordlists, are used.…”
Section: Research Framework and Included Variablesmentioning
confidence: 99%